Design and Development of VariScan: A Continuous Heart Rate Variability Monitor - Ranjan, Aman; Megha, Megha; Deb, Sujay (2024 IEEE International Symposium on Smart Electronic Systems (iSES), 2024)
Heart Rate Variability is a widely studied physiological marker that reflects the autonomic regulation of the heart. HRV represents the autonomic nervous system's control over the heart and is crucial for cardiovascular health monitoring. Heart Rate Variability is measured using methodologies such as electrocardiography (ECG) for RR interval analysis and spectral decomposition, and photoplethysmography (PPG) for blood volume changes. Some of the existing methods use mobile health (mHealth) apps with smartphone sensors, and time-frequency analysis for comprehensive HRV dynamics assessment across various time scales. This paper presents VariScan, a device designed to provide accurate and continuous(24x7) HRV monitoring using the MAX30102 sensor with an IoT controller for data transmission. The suggested module in this paper is a low-cost non-invasive device, which can be customized and easily calibarated based on the user applications. VariScan was tested on 10 subjects to predict the HR at five different time instants, and the marked reading was compared with an available heart rate meter. The device HR readings were within 0.5 per cent of the accuracy.